After the Crisis : Lower Consumption Growth But Narrower Global Imbalances? - Ohnsorge, Franziska (IMF Working Papers; Working Paper ;, 2010)
We estimate consumption dynamics in the G-7 economies, paying particular attention to the possibility of precautionary behavior in the face of uncertainty. We find that in the short run, continued income uncertainty will significantly dampen consumption growth. As such, consumption in the G-7 economies is unlikely to be the engine that revives global growth. Differences in the pace and timing of consumption moderation have implications for the evolution of global imbalances. With the U.S. experiencing a sharper rise in unemployment and, perhaps, more widespread loss of financial wealth than elsewhere in the G-7, the relative rise of the U.S. savings rate is helping narrow global imbalances. But with a likely earlier recovery in the U.S., this narrowing could be short-lived. Moreover, long-term differences- in economic and financial volatility and in demographic structures-have been an important source of the imbalances and could soon reassert their prominence.